Development and energy balance of sugarcane in the norte fluminense, Brazil - Esteves, Barbara dos Santos; de Sousa, Elias Fernandes; Mendonca, Jose Carlos; Lousada, Lidiane de Lima; Muniz, Rodrigo de Almeida; Marciano, Claudio Roberto [UNESP]; Siqueira, David Pessanha (Interciencia, 2012)
The growing concern for renewable and cleaner energy sources has increased the demand for biofuels, pointing out the ethanol from sugarcane. The aim of this study was quantify the partition of energy balance components and monitor the physiological development indexes of the sugarcane, relating them to water availability conditions of climate and soil in Campos dos Goytacazes, Norte Fluminense, Brazil. To this end, a micrometeorological station was settled in an area of 13 ha in commercial cultivation. The culture was regularly monitored at 85, 102, 128, 149, 174, 194, 215, 235, 255 and 280 days after cutting (DAC). The variations in water availability directly influenced the rates of crop growth and energy balance. Under the conditions studied most of the available energy (53%) was consumed by the latent heat flux.